Pengaruh Teknologi Produksi, Media Sosial, Jaringan Usaha dan Inklusi Keuangan Terhadap Kinerja UMKM Jenang di Desa Kenep Sukoharjo - Meygan Pramesti; Bambang Widarno (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze and clarify the influence of production technology, social media, business networks, and financial inclusion on the performance of Jenang Micro, Small, and Medium Enterprises (MSMEs) in Kenep Village, Sukoharjo. As one of the creative industry centers supporting the local economy, Jenang MSMEs in Kenep Village face significant challenges in maintaining their existence and increasing competitiveness amidst modernization. The research methodology employed is a quantitative approach using a survey method. Data were collected through structured questionnaires distributed to jenang entrepreneurs in the research location. The data analysis technique applied is multiple linear regression analysis to test the partial and simultaneous effects of the variables studied. The results show that, partially, production technology has a positive and significant effect on MSME performance by improving the efficiency of the jenang production process. Social media is proven to be a strategic tool in expanding market reach and increasing brand awareness. Business networks contribute significantly to the ease of accessing raw materials and exchanging business information, while financial inclusion facilitates entrepreneurs in capital management and access to formal financial institutions. Simultaneously, these four variables have a strong influence on determining the success of MSME performance from both financial and operational aspects. The implications of this study emphasize the importance of synergy between the adoption of appropriate technology and digital as well as financial literacy for MSME actors. Local governments and relevant agencies are expected to provide continuous assistance to strengthen the business ecosystem in Kenep Creative Tourism Village so that it can compete in the national market.